2013
DOI: 10.1097/prs.0b013e31829586e2
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Autologous Breast Reconstruction in the Context of Radiation Therapy

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 16 publications
0
44
0
3
Order By: Relevance
“…Results from Nouri et al suggest that lithium improves sciatic nerve regeneration after a traumatic lesion [72]. Additional evidence indicates that lithium exhibits synergistic effects in combined therapies with glial-derived neurotrophic factor in a model of rat sciatic nerve injury [23] and enhances the regenerative capacity of spinal motorneurons in a rat model of brachial plexus root avulsion [73]. To conclude, lithium’s pharmacology and biological effects in human patients have been extensively documented and its benefits on the central and peripheral nervous systems are seemingly clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from Nouri et al suggest that lithium improves sciatic nerve regeneration after a traumatic lesion [72]. Additional evidence indicates that lithium exhibits synergistic effects in combined therapies with glial-derived neurotrophic factor in a model of rat sciatic nerve injury [23] and enhances the regenerative capacity of spinal motorneurons in a rat model of brachial plexus root avulsion [73]. To conclude, lithium’s pharmacology and biological effects in human patients have been extensively documented and its benefits on the central and peripheral nervous systems are seemingly clear.…”
Section: Discussionmentioning
confidence: 99%
“…Additional benefits of lithium therapy include neuroprotective [14,15], anti-inflammatory [16] and anti-apoptotic effects [17], which have been exploited to treat central nervous system trauma [18,19] and chronic neurodegenerative diseases, such as Huntington’s disease, amyotrophic lateral sclerosis and Parkinson’s disease [20,21]. In the peripheral nervous system, it has been shown that lithium administration can foster functional recovery and re-myelination after injury [22,23]. Evidence from in vitro studies has been provided indicating that lithium enhances SC proliferation [24] and myelin gene expression [25,22].…”
Section: Introductionmentioning
confidence: 99%
“…For each group, half was euthanized at 6 weeks, and the other at 12 weeks. We used postmortem histomorphometric analysis as a reference to justify results derived from the CatWalk system since histomorphometric analysis is widely used in current studies as a gold standard for evaluating recovery following sciatic nerve injury (Gan et al, 2016; Kabiri et al, 2015; Lin et al, 2013). We have described the methods of histomorphometric analysis in past studies (Johnson et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…However, the impact of prior implant reconstruction on outcomes of autologous conversion remains unclear. Planned autologous conversion after immediate tissue expander reconstruction and adjuvant radiotherapy, termed delayed-immediate reconstruction, has been described by several studies as a method of preserving the tissue envelope while avoiding deleterious effects of radiation on the flap [31][32][33] . In a series of 16 delayedimmediate reconstructions, Kronowitz et al…”
Section: Discussionmentioning
confidence: 99%